The spatiotemporal variations of microbial community in relation to water quality in a tropical drinking water reservoir, Southmost China - Wu, Di; Zou, Ying; Xiao, Juan; Mo, Ling; Lek, Sovan; Chen, Bo; Fu, Qiongyao; Guo, Zhiqiang (Frontiers in Microbiology, 2024)
It is well known that water quality has great significance on microbial community composition in aquatic environments. In this study, a typical tropical reservoir was used as a model system to test the hypothesis that the variations of water quality across time and space resulted in significant differences in microbial community composition. Specifically, we detected water column indicates the microbial community composition of nine sampling sites over two seasons using Illumina TruSeq sequencing in Songtao Reservoir, Hainan Province, Southmost China. The study indicated that the dominant phylum was Actinobacteria, Proteobacteria, Bacteroidetes, and Cyanobacteria.The diversity parameters showed that the microbial community composition had significant spatiotemporal variations, including the significantly higher Shannon index and Simpson index upstream than those midstream and downstream. Besides, there were significantly higher Chao1 index, Shannon index, and Simpson index in winter than in summer. Principal coordinates analysis (PCoA) showed the microbial structural composition had significant seasonal differences. The results of microbial community composition Our results further revealed that the eutrophication level upstream was higher than that of midstream and downstream. The redundancy analysis (RDA) diagram indicated that the abundance of microbiology species significantly correlated with temperature, total phosphorus, Se, and Ni. Furthermore, the mantel's test showed that the temperature and total phosphorus significantly affected the community composition of archaea and bacteria. Overall, our finding here partially validated our hypothesis that the spatiotemporal variations of microbial community composition are significantly related to nutrients, physicochemical factors and metals, which has been unknown previously in tropical drinking waterbodies. This study substantially contributed to understanding of the composition of 4 / 32 microbial community in tropical drinking water reservoirs and the main environmental driving factors in tropical zones. It also provided a reference for the management of reservoir operation to ensure drinking water safe.